A poesia no ensino fundamental: reflexões sobre a leitura literária no livro didático - Silva, Gabriel Vaz da (2022)
This research discusses poetry reading in relation to the Final Years of Elementary School. The corpus selected for the work consists of the collection “SE LIGA NA LÍNGUA Leitura, Produção de Texto e Linguagem” (ORMUNDO; SINISCALCHI, 2018), more specifically the material related to the 6th year of Elementary School. Faced with the need to read poetry in the classroom for an aesthetic, emotional and critical formation of the student, as considered by the Base Nacional Comum Curricular (BNCC, 2017), the general objective of this investigation is to question whether the selected textbook contributes to assertive practices related to this formation. The specific objectives consist of analyzing: 1) the activities of the didactic material that should help the teacher in the work with the reading of poetry in the classroom; 2) the referrals in the textbook, in line with the Base, which aim to promote fruitful reading and the formation of a critical literary reader; 3) approaches to the relationship between Portuguese language and literature, in didactic material, which – depending on the way in which it is conducted – can either promote a broader understanding of the complexity of language, or make literary language secondary as a language without direct applicability in reading and acting in the world. The theoretical framework comprises researchers and poets such as: Candido (1995); Eliot (1991); Enes Filho (2015); Faustino (1977); Jauss (1994); Jouve (2002); Paz (1982); Pinheiro (2018); Moriconi (2002); Rocha (2018); Rouxel (2013); Zilberman (1989). The results were obtained through the survey of poems and reading activities. Poems/reading activities were placed in categories according to the following criteria, namely: a) observation of poems in chapters in which the central genre of study is literary; b) observation of the poems in chapters where the central genre of study is not literary. From this, two categories were created for the exploration of poetry reading in the didactic material: 1) The study of poetry in correlation with other discursive genres. 2) The study of poetry as a central element of the chapter. With this organization, it was observed that the poems included in the first category have efferent reading activities and guidelines (ENES FILHO, 2015), according to which the predominant characteristics are the reading residues, they do not promote a lived experience with poetry. In the second category, the guidelines on the poetic genre are more punctual and careful. However, there are few guidelines and reading activities that effectively promote an experience of pleasure with poetry.